The Analysis of Indonesia’s International Business - Annisa Edelia; Nuri Aslami (Indonesian Journal of Multidisciplinary Science, 2021)
International Business is a business whose activities pass the borders of the country. This definition includes not only international trade and overseas manufacturing, but also a thriving service industry in areas such as transportation, tourism, banking, advertising, construction, retail trade, large trade and mass communications. International marketing is different from International Business, International Trade is an inter-state transaction usually done by traditional way that is by way of export and import. With the export and import transactions, there will be a balance of tread, while international marketing which is the state of a company can be involved in a business transaction with other countries, other companies or the general public abroad. This international business transaction is generally an attempt to market overseas production. Stages in entering into international business: Incidental exports, Active Exports, License Sales, Franchising, Marketing outside the country, Production and Marketing Abroad. The obstacles in conducting international business are: Different Foreign Currencies, Low Resource Quality, Difficult State Payments and Great Risks, The existence of Import Policy of a State, The War, The existence of Regional Economic Organizations.